Concentration bias in intertemporal choice - Markus Dertwinkel-Kalt; Holger Gerhardt; Gerhard Riener; Frederik Schwerter; Louis Mick Strang (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Many intertemporal trade-offs are unbalanced: while the advantages of options are concen- trated in a few periods, the disadvantages are dispersed over numerous periods. We provide novel experimental evidence for 'concentration bias', the tendency to overweight advantages that are concentrated in time. Subjects commit to too much overtime work that is dispersed over multiple days in exchange for a bonus that is concentrated in time: concentration bias increases subjects' willingness to work by 22.4% beyond what standard discounting models could account for. In additional conditions and a complementary experiment involving mon- etary payments, we study the mechanisms behind concentration bias and demonstrate the robustness of our findings.
Keywords: D01; 330; Attention; Focusing; Bounded rationality; Intertemporal choice; Future bias; Present bias; Framing